2014
DOI: 10.1105/tpc.113.115220
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Features Determining Flower-Promoting Activity of Arabidopsis FLOWERING LOCUS T

Abstract: In Arabidopsis thaliana, the genes FLOWERING LOCUS T (FT) and TERMINAL FLOWER1 (TFL1) have antagonistic roles in regulating the onset of flowering: FT activates and TFL1 represses flowering. Both encode small, closely related transcription cofactors of ;175 amino acids. Previous studies identified a potential ligand binding residue as well as a divergent external loop as critical for the differences in activity of FT and TFL1, but the mechanisms for the differential action of FT and TFL1 remain unclear. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
266
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(275 citation statements)
references
References 65 publications
(119 reference statements)
8
266
0
1
Order By: Relevance
“…Genetic analyses revealed that late flowering in many Arabidopsis ft mutants often resulted from a dysfunctional AtFT with single amino acid substitution such as G171E in ft-1, R119H in ft-3, E84K in ft-4, and P94L in ft-6. A number of AtFT alleles with specific point mutations were further characterized through an intensive mutagenesis program (Ho and Weigel, 2014). While these studies were elegantly performed and extremely informative, a more rapid and less labor-intensive flowering assay would make it easier to efficiently evaluate the contribution of each of the 175 amino acids to the florigenic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analyses revealed that late flowering in many Arabidopsis ft mutants often resulted from a dysfunctional AtFT with single amino acid substitution such as G171E in ft-1, R119H in ft-3, E84K in ft-4, and P94L in ft-6. A number of AtFT alleles with specific point mutations were further characterized through an intensive mutagenesis program (Ho and Weigel, 2014). While these studies were elegantly performed and extremely informative, a more rapid and less labor-intensive flowering assay would make it easier to efficiently evaluate the contribution of each of the 175 amino acids to the florigenic activity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent elegant study through PCR-based random mutagenesis coupled with large-scale Arabidopsis transformation identified 33 unique mutations that influence AtFT activity among approximately 36,000 mutated AtFT alleles. Specific point mutations of E109, Y138, Q140, or N152 can convert AtFT into a TFL1-like floral repressor (Ho and Weigel, 2014). Nonetheless, this is a very timeconsuming approach, whereas VIF offers the potential of an alternate rapid, efficient, and less labor-intensive flowering assay to evaluate the influence of each amino acid residue, as well as the effect of epitope tags on florigenic activity.…”
mentioning
confidence: 99%
“…Additionally, random mutagenesis of conserved amino acids shed light on important amino acid residues and domains in these PEBP proteins (Hanzawa et al, 2005;Ho and Weigel, 2014). In this study we exchanged conserved amino acids that are assumed to be important for the flowering activating FT function and that are naturally occurring in tulip TgFT2 but only partially in TgFT3.…”
Section: The Power Of Amino Acid Substitutions In Tgft2 and Tgft3 Andmentioning
confidence: 99%
“…In this study we exchanged conserved amino acids that are assumed to be important for the flowering activating FT function and that are naturally occurring in tulip TgFT2 but only partially in TgFT3. In the study of Ho and Weigel (2014), it was shown that changing Leu-128 into a charged Lys in the AtFT protein resulted in a late flowering phenotype upon overexpression, mimicking weak TFL1 activity. TgFT2 with L128E substituted also undergoes a change from a hydrophobic to a charged residue, which in combination with the (Pin and Nilsson, 2012), PtFT1 in poplar (Hsu et al, 2011) and AcFT2 in A. cepa (Lee et al, 2013).…”
Section: The Power Of Amino Acid Substitutions In Tgft2 and Tgft3 Andmentioning
confidence: 99%
See 1 more Smart Citation